Tim Cook : the genius who took apple to the next level - Kahney, Leander (Portfolio/Penguin, 2019)
The death of Steve Jobs left a gaping void at one of the most innovative companies of all time. Jobs wasn't merely Apple's iconic founder and CEO; he was the living embodiment of a global megabrand. It was hard to imagine that anyone could fill his shoes--especially not Tim Cook, the intensely private executive who many thought of as Apple's "operations drone." But seven years later, as journalist Leander Kahney reveals in this definitive book, things at Apple couldn't be better. Its stock has nearly tripled, making it the world's first trillion dollar company. Under Cook's principled leadership, Apple is pushing hard into renewable energy, labor and environmentally-friendly supply chains, user privacy, and highly-recyclable products. From the massive growth of the iPhone to lesser-known victories like the Apple Watch, Cook is leading Apple to a new era of success.